PTU-093a An Audit of Primary Prophylaxis Against Variceal Bleeding Amongst Patients with Cirrhosis. (17th August 2016) - Johnson, C; Todd, S; McPherson, S; Masson, S
Abstract : Introduction: Variceal bleeding occurs in 30–50% of patients with portal hypertension with early mortality (within 6 weeks) after a first variceal bleed approaching 20%. 1 In 2015, the updated BSG guidelines recommend that all patients with cirrhosis should be screened for varices at diagnosis. 1 Primary prophylaxis with non-selective beta-blockers (NSBB) or variceal band ligation (VBL) should be offered to those with grade 2–3 oesophageal varices, or any varices with red signs. Appropriate endoscopic surveillance intervals are recommended for the others. Here, we aim to audit the implementation of these recommendations in our patient cohort. Methods: Between January and March 2015, consecutive patients with cirrhosis who attended specialist liver clinics at our institution were included. Clinical, demographic and endoscopic data was collected retrospectively. Results: 111 patients (50 alcohol-related liver disease [ARLD], 25 non-alcoholic steatohepatitis [NASH], 25 viral hepatitis and 11 others) were studied. The mean age was 61±12 and 68 (61%) were male. The Child's-Pugh score was A: 93 (84%), B: 15 (14%) and C: 3 (2%). Upon diagnosis of cirrhosis, 64 (58%) patients underwent endoscopic variceal screening; varices were detected in 37 (34%). Variceal screening at diagnosis was higher amongst NASH (80%) and viral hepatitis (64%) than ARLD (43%). Amongst those with varices (n = 37), primary prophylaxis was warranted in 28 and given in 27 (96%). After initiation, NSBB were rarely titrated according to clinical response. Amongst those requiring interval variceal screening or surveillance (n = 70), 40 (57%) underwent correctly-timed endoscopy. This was higher amongst NASH (71%) and viral hepatitis (69%) than ARLD (24%). Variceal haemorrhage occurred in 7 (6%) patients, 3 (43%) of whom had never undergone any endoscopic screening. Conclusion: Our results demonstrate room for greater adherence to the guidelines with regards to initial screening and subsequent surveillance endoscopy. Once varices are identified, primary prophylaxis is initiated in the majority of patients, though with little evidence of subsequent titration to clinical response. Varices screening and appropriate primary prophylaxis is a proposed quality indicator in cirrhosis care. In order to improve quality of care, we highlight the need to perform screening endoscopy at diagnosis, and to titrate primary prophylaxis after initiation. Reference: 1 Tripathi D, et al . UK guidelines on the management of variceal haemorrhage in cirrhotic patients. Gut 2015;0 :1–25. Disclosure of Interest: None Declared